A Novel Directed Evolution Method to Enhance Cell-Type Specificity of Adeno-Associated Virus Vectors - Marsch, Stephan; Huber, Anke; Hallek, Michael; Buning, Hildegard; Perabo, Luca (Combinatorial Chemistry & High Throughput Screening, 2010)
Clinical application of viral vectors is often hampered by the lack of selectivity of viral particles for the targeted tissue. This drawback decreases the efficiency of gene delivery and raises safety concerns. We successfully established a novel in vitro evolution protocol to engineer adeno-associated virus vectors with increased selectivity for designated target cells. Subjecting a peptide-display library of AAV capsids to negative selection cycles on human primary fibroblasts and to positive selection cycles on a human melanoma cell line, we isolated several variants with up to 3.7-fold increased specificity for malignant cells in comparison to fibroblasts and other cell types. These mutants can be used to achieve high levels of gene transfer to target cells reducing undesired transduction of neighbouring tissues.
Keywords: melanoma